Law and activation: two keys of development - Zabaleta Areta, Gema (Cuadernos de Trabajo Social, 2012)
The Basque Autonomous Community is undertaking an active process of policy development, service planning and organizational change with two main objectives that will progressively lead to the consolidation of the Basque Social Service System and the Basque System of Minimum Income Guarantees and Social Inclusion. The first of these two objectives is to guarantee that the right to social services, as proclaimed by the Social Services Act (2008), is made effective. This makes control of the Social Service Description List the central axis of policy development, and the Social Services Map the core of strategic planning. The second basic objective of the process undertaken is to put employment at the center of social inclusion, as established in the Minimum Income Guarantee and Social Inclusion Act (2008). In order to achieve this goal, legal reform has been undertaken which has transferred the essential components of the System, those being the management and processing of the Minimum Income Support and its complementary housing benefit, as well as the signing and monitoring of contracts for active inclusion, to the area of employment. This organizational change intends to provide the System with better instruments to achieve inclusion, which is the System’s final objective. It also makes visible and reinforces a change in strategy that brings the Basque model closer to prevailing European approaches.
Keywords: Right to social services and social benefits; Services and Benefits Description List; Planning and mapping of services; Management and administration of minimum income benefits; Activation measures.